Is Ego Depletion Real? An Analysis of Arguments. (May 2019) - Friese, Malte; Loschelder, David D.; Gieseler, Karolin; Frankenbach, Julius; Inzlicht, Michael
An influential line of research suggests that initial bouts of self-control increase the susceptibility to self-control failure (ego depletion effect). Despite seemingly abundant evidence, some researchers have suggested that evidence for ego depletion was the sole result of publication bias and p -hacking, with the true effect being indistinguishable from zero. Here, we examine (a) whether the evidence brought forward against ego depletion will convince a proponent that ego depletion does not exist and (b) whether arguments that could be brought forward in defense of ego depletion will convince a skeptic that ego depletion does exist. We conclude that despite several hundred published studies, the available evidence is inconclusive. Both additional empirical and theoretical works are needed to make a compelling case for either side of the debate. We discuss necessary steps for future work toward this aim.